DC-SIGN signalling induced by Trichinella spiralis products contributes to the tolerogenic signatures of human dendritic cells - Cvetkovic, Jelena (Sci Rep, 2020)
Tolerogenic dendritic cells (tolDCs) are central players in the maintenance of immune tolerance and thereby have been identified as the most favourable candidates for cell therapy of autoimmune diseases. We have recently shown that excretory-secretory products (ES L1) released by Trichinella spiralis larvae induce stable human tolDCs in vitro via Toll-like receptor 2 (TLR2) and TLR4. However, engagement of these receptors did not fully explain the tolerogenic profile of DCs. Here, we observed for the first time that dendritic cell-specific ICAM-3 grabbing non-integrin (DC-SIGN) interacts with highly glycosylated ES L1 and contributes to the generation of ES L1-induced tolDCs. Blocking DC-SIGN interfered with the ES L1-induced higher expression of CD40 and CCR7 and the production of IL-10 and TGF-β by DCs. The cooperation of TLR2, TLR4 and DC-SIGN receptors is of importance for the capacity of DCs to prime T cell response toward Th2 and to induce expansion of CD4+CD25+Foxp3+ T cells, as well as for the production of IL-10 and TGF-β by these cells. Overall, these results indicate that induction of tolDCs by ES L1 involves engagement of multiple pattern recognition receptors namely, TLR2, TLR4 and DC-SIGN.